Bayesian inference of species diffusion in the West African Agama agama species group (Reptilia, Agamidae). Issue 3 (4th May 2017) - Leaché, Adam D.; Grummer, Jared A.; Miller, Michael; Krishnan, Sneha; Fujita, Matthew K.; Böhme, Wolfgang; Schmitz, Andreas; Lebreton, Matthew; Ineich, Ivan; Chirio, Laurent; Ofori-boateng, Caleb; Eniang, Edem A.; et al.
Abstract : The savannah and tropical forest biomes of Africa have a long history of expansion and contraction, and the recent and rapid spread of dry savannah habitats has influenced the spatial and temporal diversification of vertebrate taxa across this region. We used a combination of species tree and phylogeographic methods to describe the spatio-temporal changes through time and across space (= species diffusion) in a clade of seven West African lizard species in the Agama agama species group. A Bayesian species tree diffusion approach was used to compare the relative rates at which species ranges changed across the landscape. We found that some species have high diffusion rates characterized by significant movement in their range location and minor changes to their overall range size, whereas other species show little movement in their range centre with an exponential increase in range size. This discrepancy between the rates that range locations shift versus change in their relative area could be linked to populations tracking their preferred habitats through time. A continuous Bayesian phylogeography approach using a relaxed random walk model was used to estimate the timing and rate of population size change and geographic diffusion in A. picticauda, the single species in the group with an extensive African distribution from Mauritania to Ethiopia. The mean dispersal rate of A. picticauda increased dramatically throughout the Pleistocene, and a Bayesian skyride analysis supports exponential population growth over this same time period. A comparison of genetic diversity across different loci and species suggests that A. lebretoni experienced a mitochondrial selective sweep that has caused a deficit of variation at this locus in relation to nuclear loci.